Body image flexibility and its correlates: A meta-analysis. (June 2021) - Linardon, Jake; Anderson, Cleo; Messer, Mariel; Rodgers, Rachel F.; Fuller-Tyszkiewicz, Matthew
Highlights: A meta-analysis of 56 studies on body image flexibility and its correlates was conducted. Body image flexibility was associated with lower levels of eating pathology, body image problems, and psychopathology. Body image flexibility was consistently associated with higher levels of positive psychological constructs. Males reported significantly higher levels of body image flexibility than females. The potentially adaptive role of body image flexibility was supported. Abstract: Body image flexibility refers to the ability to openly experience thoughts or feelings about the body without acting on them or trying to change them. Accumulating evidence has demonstrated that body image flexibility is connected to numerous adaptive processes, and that it is sensitive to change during psychological interventions. However, a quantitative synthesis of empirical research on body image flexibility is lacking. We conducted the first meta-analysis on body image flexibility and its correlates. Sixty-two studies were included. Random effects meta-analyses were conducted on 19 psychological correlates, divided into three clusters: eating and body image disturbances, positive body-related and general psychological constructs, and general psychopathology. Meta-analyses showed inverse correlations between body image flexibility and each construct within the eating and body image disturbances cluster ( r s= −.45 to −.67), and the general psychopathology cluster ( r s= −.37 to −.58). Body image flexibility was positively associated with each positive psychology construct ( r s = .23 – .58). Men reported higher levels of body image flexibility than women ( d = 0.32). Psychological interventions were more effective than control groups at enhancing body image flexibility in randomized controlled trials ( d = 0.42). Findings confirm that body image flexibility is consistently connected to indices of mental health, and that it can be enhanced during psychological interventions.